Early Post-Operative Outcome of Post Placental Intrauterine Contraceptive Device during Caesarean Section: A Prospective Analytical Study - Akther, Shahanaj; Nessa, Kamrun; Rehena, Zeenat; Reza, Tamanna Ferdous; Hira, Hasina Momotaj; Ilias, Md (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Institutional delivery has been increased all over the country, thereby providing opportunities for quality post-partum family planning services. Intrauterine Immediate post-placental IUCD insertion at the time of Caesarean Section (CS) has been recommended by WHO but is not still well accepted. The aim of this study was to determine the early postoperative outcome of postplacental intrauterine device insertion at the time of CS and reasons for refusal to accept it. Materials and methods: This was a hospital based prospective analytical study, carried out in the Department of Obstetrics and Gynecology of Chittagong Medical College Hospital (CMCH) Chattogram, Bangladesh for one year. Study comprises of 150 women who accepted post placental insertion of a CuT 380A PPIUD (Post- Placental Intrauterine Contraceptive Device) during CS and another 150 women who did not accept the insertion of the PPIUD during CS. The incidence of excessive bleeding, severe abdominal pain, wound infection and endometritis were compared between two groups. Results: There was no significant difference in the postoperative complication rates between both the groups. Severe pain was complained by 36.7% case and 34.7% cases respectively of study and control group on 1st POD (p=0.607). Puerperal bleeding was also similar in both groups. The rates for post-operative wound infection being 6% and 7.3% in the study and control groups respectively (p=0.643) and there was no case of genital tract infection in the entire patients. Conclusion: PPIUD insertion during CS did not significantly increase postoperative pain, hospital stay, the volume or duration of bleeding, or frequency of infection. JCMCTA 2022 ; 33 (2) : 79-83